2021
DOI: 10.24925/turjaf.v9i5.887-896.4166
|View full text |Cite
|
Sign up to set email alerts
|

Geleceğin Protein Kaynağı: Yenilebilir Böcekler

Abstract: Considering of the increasing world population, the researchers are aware that protein sources may not be sufficient and focused on new protein sources. For this reason, the potential of edible insects to be used directly or as an ingredient in food has started to draw attention. Edible insects have been consumed as traditional food in Africa, Asia and South America for many years. However, especially in European countries, consumers have a negative attitude towards the consumption of insects as food. Edible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Most insects use unsuitable plant material as nutrients for agricultural byproducts. Therefore, insects do not play a negative role in the consumption of food sources compared to cows, chickens and pigs that consume human food(Dossey, Tatum, and McGill, 2016;Baş Aksoy, and El, 2021). Studies have shown that while 25 kilograms of feed is spent to produce 1 kilogram of beef, 2 kilograms of feed is spent to produce 1 kilogram of edible insects(Guine, Correia, Coelh, and Costa, 2021).While few people consumed snails, shrimp, crab, lobster, frog legs and raw fish in the early 1980s, many people today consume such products in a variety of ways.…”
mentioning
confidence: 99%
“…Most insects use unsuitable plant material as nutrients for agricultural byproducts. Therefore, insects do not play a negative role in the consumption of food sources compared to cows, chickens and pigs that consume human food(Dossey, Tatum, and McGill, 2016;Baş Aksoy, and El, 2021). Studies have shown that while 25 kilograms of feed is spent to produce 1 kilogram of beef, 2 kilograms of feed is spent to produce 1 kilogram of edible insects(Guine, Correia, Coelh, and Costa, 2021).While few people consumed snails, shrimp, crab, lobster, frog legs and raw fish in the early 1980s, many people today consume such products in a variety of ways.…”
mentioning
confidence: 99%